Pitfalls in the Construction of Demand and Supply Curves: A Reply - Leontief, Wassily W. (Quarterly Journal of Economics, 1934)
Journal Article Pitfalls in the Construction of Demand and Supply Curves: A Reply Get access Wassily W. Leontief Wassily W. Leontief Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 48, Issue 2, February 1934, Pages 355–361, https://doi.org/10.2307/1885615 Published: 01 February 1934